Le schème de l’hebdomade dans les premiers écrits de saint Augustin - Lagouanère, Jérôme (Revue d'études augustiniennes et patristiques, 2014)
The schema of the hebdomad often occurs in Augustine’s works. A biblical inspiration is commonly read in his latest works, but in his fi rst ones this schema would be influenced, according to some critics, by Varro, and, according to other ones, by neo-platonism. So, after shortly studying how this schema is dealt by some contemporaries of Augustine, we analyse how this latter can be understood as a spiritual structure of the De ordine and the De quantitate animae. Finally, we conclude that a porphyrian influence must be probable.